Investigating The Impact of Pruritus on The Quality of Life of the Elderly in Surakarta Nursing Home - Oktavriana, Triasari; Mawardi, Prasetyadi; Murastami, Ammarilis; Murasmita, Alamanda; Pradestine, Sesia; Putri, Osdatilla Esa; Lidjaja, Lifesia Natali; Alia, Vrenda; Kusumasari, Nila (Health and Medical Journal, 2025)
Background: The elderly population has been growing rapidly in recent decades. Research has shown that the prevalence of itching (pruritus) increases with age, with 20.8% of individuals aged 60-69 years experiencing it, 22.9% for those aged 70-79 years, and 26% for those aged 75 years and above. Assessing the skin's barrier function by measuring transepidermal water loss (TEWL) using a tool called a Tewameter is important for objectively evaluating dry skin, which is the most common cause of itching in the elderly. It's important to understand how itching affects the quality of life of the elderly, particularly in nursing homes. Objective: This study aims to determine how itching affects the quality of life of the elderly in nursing homes in Surakarta City, especially at PMI Peduli and Aisyiyah Nursing Homes. Methods: This research used an observational, cross-sectional design. Data was collected through interviews using the 5D itch scale questionnaire, and the quality of life was measured using the DLQI (Dermatology Life Quality Index) questionnaire. TEWL levels were also measured using a Tewameter. Results: 29 subjects participated in the interviews, with 69% being women and 31% being men. Most subjects were aged 60-69 years (41%), and the most common comorbidity was hypertension (41%). The 5D Itch Scale questionnaire revealed that itching affected the subjects for less than 6 hours daily (66%), and during the last 2 weeks, itching did not significantly impact the subjects' activities, including sleep, hobbies, housework, and work (51%-69%). The most common location of itching was the back (14%). The DLQI data showed that itching had a severe impact on the subjects (65.5%), followed by a moderate impact (24.1%), and a very severe impact (10.3%). TEWL data indicated that all subjects had an increase of >10 g/h/m2. Conclusion: The study found that itching had a mild impact on the lives and activities of the subjects in general, lasting for less than 6 hours a day. The statistical results showed a positive and significant relationship between the intensity of itching and the quality of life of the elderly with pruritus.